Respuesta :
Answer:
x=-1
Step-by-step explanation:
3(x−4)=15x
Use the distributive property to multiply 3 by x−4.
3x−12=15x
Subtract 15x from both sides.
3x−12−15x=0
Combine 3x and −15x to get −12x.
−12x−12=0
Add 12 to both sides. Anything plus zero gives itself.
−12x=12
Divide both sides by −12.
x=
−12
12
Divide 12 by −12 to get −1.
x=−1
Answer:
[tex]3(x- 4)=15x[/tex]
[tex]3x-12=15x[/tex]
[tex]3x-12+12=15x+12[/tex]
[tex]3x=15x+12[/tex]
[tex]3x-15x=15x+12-15x[/tex]
[tex]-12x=12[/tex]
[tex]\frac{-12x}{-12}=\frac{12}{-12}[/tex]
[tex]x=-1[/tex]